301 - The diagnostic and treatment challenges of behavioral and psychological symptoms in Alzheimer's disease; a qualitative study in memory clinic practice. (October 2020) - Eikelboom, Willem S.; Coesmans, Michiel; Ossenkoppele, Rik; van den Berg, Esther; Papma, Janne M.
Abstract : Introduction: Behavioral and psychological symptoms in dementia (BPSD) have great impact on the daily lives of Alzheimer's disease (AD) patients and their caregivers. Timely recognition and treatment of these symptoms may benefit quality of life, caregiver burden, and delay disease progression. In this qualitative study we examine the experiences of memory clinic physicians with the recognition and management of BPSD in early stages of AD. Methods: Semi-structured interviews were held with 8 physicians (5 neurologists, 3 geriatricians) employed at memory clinics of academic or general hospitals in the Netherlands. Two independent researchers coded verbatim transcripts of the interviews, followed by a consensus meeting on preliminary themes. In the upcoming months, additional interviews will be conducted until data saturation is reached. Results: Preliminary results indicate substantial variability in how memory clinic physicians recognize and diagnose BPSD in AD. Themes are: 1. Prevalence of BPSD in early stages of AD; e.g. 'BPSD is more often present in late stages of AD […]' vs. 'I see this often, very often, I think these are the main problems people with AD face'). 2. Systematic assessment; some physicians consider it part of their clinical work-up to assess behavioral changes while other physicians do not touch upon BPSD. 3. Barriers for assessment; e.g. a lack of time, and not being able to observe BPSD occurring at home in a memory clinic setting. Treatment and management of BPSD in AD also differed greatly. Themes are 1. Treatment type; Two physicians discussed using a person-centered non-pharmacological approach, others refer patients with BPSD to daycare, a case manager or psychiatrist, or treat 'problematic' behaviors with psychotropic drugs. 2. Capabilities; some physicians experience managing BPSD in AD as very difficult, while others are confident about their capabilities. The majority suggests that collaboration with GPs or case managers may benefit treating these complex symptoms. Conclusion: There are remarkable differences in the recognition and management of BPSD in patients with AD visiting memory clinics in the Netherlands. Considering the potential benefit of early recognition and treatment, a first crucial step is discussing standardization of recognition and management of BPSD in memory clinics.